Diagnostic value of selected fetal echocardiographic parameters in the prenatally suspected bicuspid aortic valve - Min Zheng; Yanping Ruan; Lin Sun; Xiaowei Liu; Jiancheng Han; Yihua He (Echo Research and Practice)
Abstract Objective To explore the diagnostic value of crucial parameters of echocardiography for fetal bicuspid aortic valve (BAV) and improve diagnostic accuracy. Methods Fetuses with a prenatal suspected diagnosis of BAV were followed, and confirmed and misdiagnosed cases were obtained. Prenatal echocardiography was reviewed and analyzed. ROC curves were plotted to evaluate the diagnostic capabilities of different echo signs. Results 14 cases were confirmed, and 7 patients were misdiagnosed. Some abnormal ultrasound signs were observed in both groups, including direct ultrasound signs of the aortic valve: Two commissures and a “fish-mouth” opening; Thickening, hyperechogenicity, or the presence of a raphe; Restricted motion or opening; Eccentric or a-linear valve leaflet closure line and indirect ultrasound signs: Increased supra-aortic valve velocity; Post-stenotic widening of the ascending aorta. The combination of “Increased supra-aortic valve velocity” and “Two commissures and a ‘fish-mouth’ opening” had the highest AUC (AUC: 0.893, 95%CI: 0.752-1.000, Sensitivity: 0.786, Specificity: 1.000). Conclusions We first found that the combination of “Increased supra-aortic valve velocity” and “Two commissures and a ‘fish-mouth’ opening” had the best diagnostic capability and could reduce the rate of misdiagnosis. Fetuses with BAV should be followed up prenatally for the aortic valve and ascending aorta as they progressively deteriorate with gestational age.